노인들의 식품위생·안전에 대한 인식, 지식과 행동에 관한 연구 - 이미숙(Mi Sook Lee); 이심열(Sim-Yeol Lee) (Korean journal of community nutrition, 2021)
Objectives: This study was conducted to investigate the awareness, knowledge, and behavior about food hygiene·safety among the elderly, and to provide basic data on this for their healthy dietary life. Methods: The study was conducted through a survey using a self-administered questionnaire on 473 elderly people over 60 years old living in Seoul and Gyeonggido. The questionnaire was designed to examine general characteristics, meal preparation status, the relation between awareness, knowledge, food hygiene behavior, and safety. Results: Among the particpants, 44.2% of the total people surveyed were elderly married couples, and 14.0% were single-person households. For men, most of the meals were prepared by the spouse (74.1%), and among women, 93.8% prepared their meals themselves (P < 0.001). 61.3% of the total subjects answered that they were very interested in food hygiene and safety. Men (32.4%) thought it was more difficult to collect food hygiene·safety information compared to women (14.0%, P < 0.001). The knowledge score about food hygiene·safety was 0.60 (P < 0.05) and the behavior score was 3.70 (P < 0.001). The correlation coefficient between knowledge and behavior according to food hygiene·safety was 0.371 (P < 0.001). Conclusions: The food hygiene·safety behavior of the elderly was associated with knowledge (P < 0.001). Therefore, food hygiene·safety education is necessary to ensure information availability and promote the health of the elderly.